A framework for equitable virtual rehabilitation in the metaverse era: challenges and opportunities - Veras, Mirella; Labbé, David R.; Furlano, Joyla; Zakus, David; Rutherford, Derek; Pendergast, Barry; Kairy, Dahlia (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Metaverse technology is spurring a transformation in healthcare and has the potential to cause a disruptive shift in rehabilitation interventions. The technology will surely be a promising field offering new resources to improve clinical outcomes, compliance, sustainability, and patients’ interest in rehabilitation. Despite the growing interest in technologies for rehabilitation, various barriers to using digital services may continue to perpetuate a digital divide. This article proposes a framework with five domains and elements to consider when designing and implementing Metaverse-based rehabilitation services to reduce potential inequalities and provide best patient care. Methods: The framework was developed in two phases and was informed by previous frameworks in digital health, the Metaverse, and health equity. The main elements were extracted and synthesized via consultation with an interdisciplinary team, including a knowledge user. Results: The proposed framework discusses equity issues relevant to assessing progress in moving toward and implementing the Metaverse in rehabilitation services. The five domains of the framework were identified as equity, health services integration, interoperability, global governance, and humanization. Discussion: This article is a call for all rehabilitation professionals, along with other important stakeholders, to engage in developing an equitable, decentralized, and sustainable Metaverse service and not just be a spectator as it develops. Challenges and opportunities and their implications for future directions are highlighted.